Level of HIV serodiscordance and associated factors among heterosexual couples in Ethiopia: A systematic review and meta-analysis. - Dagne Deresa Dinagde; Hana Tadesse Afework; Habtamu Wana Wada; Meserat Workiye Negash (Public Library of Science (PLoS), 2024)
HIV-related causes accounted for approximately 770,000 deaths globally in 2018. Globally, there were 1.7 million new infections, and approximately 37.9 million people were living with HIV by the end of 2018. According to the WHO 2018 study, the African Region was the most affected, with 25.7 million people living with HIV in 2018. In Africa, married and cohabiting couples have a high prevalence of HIV discordance, ranging from 3% to 20% in the general population. Therefore, it is crucial to understand the level of HIV serodiscordance among married couples in Ethiopia and the contributing factors. Studies were systematically searched, utilizing international databases such as PubMed, Google Scholar, Cochrane Library, and Embase. The level of quality of the included articles, which employed cross-sectional and cohort study designs, was evaluated using the New Castle Ottawa scale. The systematic review employed a random-effects approach, and statistical analysis was conducted using STATA version 17 software. The presence of statistical heterogeneity within the included studies was assessed using the I-squared statistic. The random-effects meta-analysis model was used to estimate the pooled level of HIV serodiscordance. The results were reported following the Preferred Reporting Item for Systematic Review and Meta-Analyses (PRISMA) guideline. A total of ten (10) observational studies were included in this review. The pooled level of HIV serodiscordance among married heterosexual couples in Ethiopia was found to be 11.4% (95% CI = 7% -15.7%). The results from the meta-analysis indicated a significant positive association between HIV serodiscordance and the variables studied. Specifically, consistently using condoms (OR = 1.82; 95% CI: 1.08-2.56), having a CD4 count of >200 cells/mm3 (OR = 1.45; 95% CI: 1.12-1.77), and having a premarital sexual relationship (OR = 1.93; 95% CI: 1.28-2.57) were strongly linked to couples' serodiscordance. To protect a seronegative partner in a serodiscordant relationship from acquiring HIV infection, it is crucial to implement preventive measures. These measures include providing comprehensive health education on the correct and consistent use of condoms, ensuring regular monitoring and care at an antiretroviral therapy (ART) clinic, and offering voluntary counseling and testing (VCT) services to both sexual partners.